Àlles wàs glanzt ìch nìt umbadingt Guld: reference accents, inner circle Englishes and language attitudes in Alsace. Issue 2 (7th February 2023) - McInerney, Erin
ABSTRACT: The many permutations of spoken English have called for an interrogation into the notions of 'standard English' and 'native accents'. Despite their problematic nature, these terms remain commonly used, and familiarity with 'standard', inner-circle varieties of English is typical among L2 English speakers, differences in education and language policy notwithstanding. This paper inquires into student language attitudes in Alsace, a region with a long and complex language tradition. A mixed-methods model was used to gather seven students' reactions towards four inner-circle Englishes (Received Pronunciation, Standard American English, Glaswegian English, African American English). Findings revealed student preference for the two American speakers as well as preferential ratings linked to comprehensibility of speakers and a range of past experiences. Other findings favour those of previous language attitude studies in which RP and SAE outperform other samples in areas of education and prestige. GE and AAE samples were associated with both positive human characteristics and a lack of education. Overall, results indicate the need for future empirical research of this population as well as the necessity for linguists, researchers and teachers to make room for the spectrum of speakers and Englishes that lie outside of traditional reference accents.